2014
DOI: 10.5489/cuaj.2089
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of single-agent carboplatin (AUC 4) for advanced testicular seminoma safely achieved complete response in an 80-year-old man with chronic heart failure: A case report

Abstract: Cite as: Can Urol Assoc J 2014;8(11-12):e931-3. http://dx.doi.org/10.5489/cuaj.2089 Published online December 15, 2014. AbstractCarboplatin is often used instead of cisplatin as an alternative treatment for advanced testicular cancer. However, the safety, optimal dose, and optimal duration of this agent are unclear in patients with cardiac complications. We report the safety and effectiveness of long-term single-agent carboplatin for the treatment of testicular cancer in a patient with chronic heart failure (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Firstly, the patient with malignant tumor (cervical cancer stage IIB) receiving multiple courses of chemotherapy putatively developed emboli and thrombi and exhibited an imbalanced stress response. Fukuhara et al [5] demonstrated dose-dependent risks of adverse events with respect to the tumor stage; however, they did not indicate the specific risks for different stages. Secondly, the patient displayed abnormal ECG findings with ST-T segment depression and a PR interval of 0.231 seconds on multiple leads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the patient with malignant tumor (cervical cancer stage IIB) receiving multiple courses of chemotherapy putatively developed emboli and thrombi and exhibited an imbalanced stress response. Fukuhara et al [5] demonstrated dose-dependent risks of adverse events with respect to the tumor stage; however, they did not indicate the specific risks for different stages. Secondly, the patient displayed abnormal ECG findings with ST-T segment depression and a PR interval of 0.231 seconds on multiple leads.…”
Section: Discussionmentioning
confidence: 99%
“…Although ECG abnormalities were not related to cisplatin, the usage might impair the proximal tubules, reduce the reabsorptions of potassium and magnesium, shorten the duration of the action potential, decrease calcium inflow, and finally result in early systolic dysfunction. [5] Thirdly, the patient received 3 courses cisplatin. Cisplatin activates the transmembrane protein kinase RNA (PKR)-like ER kinase (PERK) signaling pathway, phosphorylates IF2a, activates caspase 3, promotes the formation of apoptosome, and induces apoptosis of the cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Between 1980 and 2017, only five clinical studies reported cardiotoxicity from cisplatin ( Hu et al, 2018 ). Cisplatin has relatively early cardiotoxic effects, mainly causing arrhythmias leading to ECG changes and chronic heart failure ( Fukuhara et al, 2014 ). Yang et al reported a decrease in left ventricular ejection fraction (LVEF) from 70% to 48% in a 53-year-old woman with cervical cancer after 3 weeks of cisplatin application ( Hu et al, 2018 ).…”
Section: Cardiotoxicity Of First-line Chemotherapy Drugs For Osteosar...mentioning
confidence: 99%
“…Cardiac toxicity percentage is less therefore very few patients reported and the mechanisms of cisplatin-induced cardiotoxicity remain unclear [5,6]. The patients with cervical cancer developed thrombus after receiving cisplatin [7]. Cisplatin activates the transmembrane protein kinase RNA (PKR)-like ER kinase (PERK) signalling pathway, phosphorylates IF2a, activates caspase, promotes the formation of apoptozole, and induces apoptosis of the cardiomyocytes [8,9].…”
Section: Introductionmentioning
confidence: 99%